Anti‐PD1 versus anti‐PD‐L1 immunotherapy in first‐line therapy for advanced non‐small cell lung cancer: A systematic review and meta‐analysis - Brito, Angelo Borsarelli Carvalho (Thorac Cancer, 2021)
BACKGROUND: Due to the increasing number of trials with immune checkpoint inhibitors (ICIs) in the first‐line therapy of non‐small cell lung cancer (NSCLC) patients, we performed a systematic review and meta‐analyses to investigate the difference between anti PD‐1 and PD‐L1 antibodies, used alone or in combination with chemotherapy, through adjusted indirect analysis to minimize the potential bias regarding overall survival (OS), progression‐free survival (PFS), overall response rate (ORR) and grade 3–5 adverse events (AEs). METHODS: A systematic review of studies reporting clinical outcomes and toxicity associated with first‐line therapy employing anti‐PD1 or anti‐PD‐L1 antibodies alone, or in combination with chemotherapy, to treat metastatic, treatment‐naïve NSCLC patients was performed. Primary outcomes were OS, PFS, ORR and grade 3–5 AEs. We used a random‐effects model to generate pooled estimates for proportions. Meta‐analyses using pooled risk ratios were performed for binary outcomes from comparative studies with the random effects model. RESULTS: A total of 13 eligible studies met our eligibility criteria, including 7673 patients. In the ICI‐chemotherapy combination subgroup, we observed that anti‐PD1 therapy was associated with better OS (p = 0.022) and PFS (p = 0.029) compared with anti‐PD‐L1 therapy. In the monotherapy subgroup, there was no statistical difference between the use of anti‐PD‐1 and anti‐PD‐L1 for OS and PFS. With regard to ORR and toxicity, in the ICI‐chemotherapy combination subgroup, we observed a trend of better ORR (p = 0.12) with the use of anti‐PD1 therapy and less frequent grade 3–5 AEs compared to the use of anti‐PD‐L1 therapy (p = 0.0302). In the monotherapy subgroup, there was no statistical difference between the use of anti‐PD‐1 and anti‐PD‐L1 regarding ORR and toxicity. CONCLUSIONS: Our study suggests that PD‐1 drug plus chemotherapy is superior to anti‐PD‐L1 plus chemotherapy for NSCLC; nevertheless, as monotherapy, both strategies appear to be similar.